PENGARUH PERTUMBUHAN EKONOMI SUMATERA UTARA PADA TAHUN 2009_2024 - Rouli Pranatalia Simanjuntak; Joko Suharianto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research aims to analyze the influence of Indonesia's economic growth during the 2009–2024 period on various macroeconomic indicators, such as unemployment rates, inflation, investment and community welfare. By using secondary data from the Central Statistics Agency (BPS), Bank Indonesia, and other relevant sources, this study adopts a quantitative approach with multiple linear regression analysis methods. The results of the research show that economic growth has a significant impact on reducing unemployment rates and increasing investment, although this is not always in line with increasing social welfare evenly. In addition, fluctuations in economic growth influenced by the 2008 global crisis, the COVID-19 pandemic, as well as political dynamics and fiscal policy have had a real impact on national economic stability. These findings emphasize the importance of inclusive and sustainable economic development strategies to maintain stability and improve long-term prosperity. economic growth in North Sumatra Province, focusing on specific periods and the factors that influence them. Data from the Central Statistics Agency of North Sumatra Province shows that North Sumatra's economic growth in the fourth quarter of 2021 reached 3.81% (y-on-y), driven by the Electricity and Gas Procurement sector, and 2.61% growth (c-to-c) overall in 2021, especially from the Information and Communication sector. However, the study also highlights the existence of economic disparities between sectors and the effect of inflation on growth. Several other studies have also examined the effect of economic growth on the Human Development Index (HDI) and factors such as poverty, unemployment, and investment. Further studies are needed to comprehensively understand the factors that drive North Sumatra's economic growth and how to optimize the potential of this region.